Unsaturated Soils. Advances in Geo-Engineering 2008
DOI: 10.1201/9780203884430.ch61
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of a silt used in flood embankment construction in Indonesia

Abstract: Oedometer tests were carried out on a silt used in flood embankment construction in Indonesia. Three test series were carried out under dry-of-optimum, wet-of-optimum and prepared wet and then dried, initial conditions. Where collapse was observed, the collapse potential for the specimen was evaluated and severity of collapse determined. This material has been sampled from embankments in East Java, Indonesia where there is a recurrent history of geotechnical failures. These preliminary results show the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The samples were obtained at depths from 0.3 m to 0.5 m from the surface with disturbed and undisturbed conditions. The soil was classified as an inorganic silt of high compressibility [6]. Some basic properties of the soil are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were obtained at depths from 0.3 m to 0.5 m from the surface with disturbed and undisturbed conditions. The soil was classified as an inorganic silt of high compressibility [6]. Some basic properties of the soil are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical composition using X-Ray Fluorescence method of the soil is shown in Table 2; it was found that the soil chemical compounds are mainly silica (Si) and Calcium (Ca). The minerals of the clay fraction play a central role in the properties of the soil, such as plasticity and strength [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation